2017
DOI: 10.1039/c7ra03828c
|View full text |Cite
|
Sign up to set email alerts
|

Topological relations and piezoelectric responses of crystal-axis-oriented BaTiO3/CaTiO3 nanocomposites

Abstract: were formed via an in situ topochemical mesocrystal conversion mechanism. The density of the artificial BT/CT heteroepitaxial interface in these mesocrystalline nanocomposites can be adjusted by regulating the fraction of BT and CT in the nanocomposites. The mesocrystalline BT/CT nanocomposite with the composition close to BT/CT ¼ 1/1 presents a large piezoelectric response owing to the lattice strain derived from its heteroepitaxial interfaces with the high density in the nanocomposite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It is preliminarily found that when the proportion of two-phase components is close to 1, it can be regarded as the maximum density of the heterogeneous epitaxial interface, and the piezoelectric properties are the highest. [147,148] Proper adjustment of the lattice mismatch rate of different binary titanate nanocomplexes could also effectively regulate the piezoelectric properties. [149][150][151] This is due to the adjustment of the binding state at the interface, such as lattice matching, interface components, stress and strain, to improve residual polarization, promote polarization rotation, and enhance the spontaneous polarization ability and domain wall motion speed.…”
Section: (23 Of 29)mentioning
confidence: 99%
“…It is preliminarily found that when the proportion of two-phase components is close to 1, it can be regarded as the maximum density of the heterogeneous epitaxial interface, and the piezoelectric properties are the highest. [147,148] Proper adjustment of the lattice mismatch rate of different binary titanate nanocomplexes could also effectively regulate the piezoelectric properties. [149][150][151] This is due to the adjustment of the binding state at the interface, such as lattice matching, interface components, stress and strain, to improve residual polarization, promote polarization rotation, and enhance the spontaneous polarization ability and domain wall motion speed.…”
Section: (23 Of 29)mentioning
confidence: 99%
“…However, in this study, the piezoresponses of BT/CT NCs were clearly obtained. Moreover, Hu et al[14] also found an increment of 2-5 times in piezoresponse of BT/CT nanocomposite compared to that of BT. It suggested that the strain induced by heterointerfaces expressed the piezoelectric property.…”
mentioning
confidence: 93%
“…This suggests that SGR plays a role similar to MPB when the size of SGR reduces. BaTiO 3 /CaTiO 3 (BT/CT) nanocomposites synthesized by solvothermal reaction were also investigated [14]. Heterointerfaces have an enhanced d 33 value approximately 5 times that of BT nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, some significant templates with anisotropic morphologies are used as precursors to yield the target with the original framework of the precursor via an in situ topochemical conversion reaction during hydrothermal treatments. ,, Some one- or two-dimensional (1D or 2D) BT crystals can be prepared from protonated titanates, such as H 1.07 Ti 1.73 O 4 ­· n H 2 O, H 2 Ti 4 O 9 ­· n H 2 O, H 2 Ti 3 O 7 , H 2 Ti 2 O 5 , and other protonated titanates, as precursors with layered structures . These precursors can react with an alkaline earth metal hydroxide to form the BT phase during the hydrothermal process. , Some 2D titanate polycrystals were developed using hydrothermal processes from titanate precursors in our previous works. ,,, Those titanate polycrystals were constructed from oriented nanocrystals and showed single-crystal diffraction points, i.e., they were mesocrystals. Although the formation mechanism and electric properties of the 2D titanate mesocrystals have been revealed, little is known about the electric properties of 1D titanate mesocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we prepared BT polycrystal using the 2D H 1.07 Ti 1.73 O 4 as the precursor for the first time . On the basis of that study, the topological relations between H 1.07 Ti 1.73 O 4 and the obtained BT-based nanocomposite mesocrystal have been investigated. ,, However, little is known about the piezoelectric response of BT obtained from this layered titanate.…”
Section: Introductionmentioning
confidence: 99%